Relation of plant height and cladode number of cactus little sweet clone consorted with pornunça - Moura, E A.; Lucena, L. R.; Leite, M. L.; Moura, G. A.; Simões, V. J.; Simplício, J. B. (Cuban Journal of Agricultural Science, 2020)
Forage cactus presents high phytomass production in semiarid regions, due to its high energy value, high non-fibrous carbohydrate contents, high acceptability, high water reserves and easy propagation. The aim of this study was to define the best relation between plant height and cladode number of Nopalea cochenillifera with and without "pornunça". The design was performed in randomized blocks, with single cacti and "pornunça" consortium, with three repetitions. The experimental unit was composed of three rows of cactus, with spacing between rows of 1.60m and between plants of 0.20m, which is equivalent to a population density of 31,250 plants ha-1. The plant height and cladode number were related through regression models, which were evaluated by four criteria of selection. There was no difference between plant height and cladode number of cactus with and without consortium. The Nopalea cochenillifera consortium with "pornunça" is promising, and it presents agronomic viability and advantages. The adoption of the hyperbolic tangent model H=80.78*tanh(0.059*DAP0.67CN-0.052) allows the explanation of the height of Nopalea cochenillifera, with high precision and low cost, depending on the age of the plant and total number of cladode per plant. Key words: growth curve, hyperbolic tangent, Nopalea cochenillifera